PENGEMBANGAN LKPD BERBASIS GEOGEBRA UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Dwi Novitasari; Andi Trisnowali MS; Deni Hamdani; Junaidi Junaidi; Sartika Arifin (Department of Mathematics Education, Universitas Kuningan, 2021)
Students usually have difficulties in visualizing images that are caused by the lack of students’ conceptual understanding. We need learning which is able to help the students’ conceptual construction. One of them is by using technology in learning. This study aimed to develop students’ worksheets using a scientific approach based on GeoGebra for the eleven-grade of senior high school in Mataram-Indonesia. This study type was Research and Development (RD) using Plom model. The developed product was validated by experts and tested for its practicality by mathematics teachers and students. The quality of the product refers to the validity and effectiveness of the product. The results of expert validation and field try out indicated that the developed worksheet is valid and practical. The result of the research showed that students’ worksheet is valid and effective with validation average score is 4.44 and effective. The students’ average score is 86.84% (above the minimum standard) and the average of students' responses is 87.72% (positive category). It can be concluded that the developed worksheet can be used in the classroom